MINAT MASYARAKAT BERTRANSAKSI MENGGUNAKAN FINANCIAL TECHNOLOGY (FINTECH) DI KOTA TANGERANG - Siti Asriah Immawati; Dadang Dadang (Universitas Muhammadiyah Tangerang, 2019)
Financial technology is the result of a combination of financial services and technology which ultimately transforms the conventional business model into a moderate one, which initially made payment systems face-to-face and brought a certain amount of cash, now can be done with long-distance transactions and can be done in a matter of just seconds. This study aims to determine the social influence, convenience, usefulness, effectiveness and risk assurance of people's interest in transacting using financial technology (Fintech). The research method used is quantitative research in the form of online surveys through website media, email and social media (Whatsapp). Where the sample was randomly selected as many as 200 respondents consisting of students, lecturers, housewives, public and private employees. The analysis used uses multiple regression analysis. The results of the analysis show that Simultaneously the benefits, convenience, social factors, effectiveness, security guarantees have the influence of interest in using fintech transactions.Keywords: benefit, convenience, social, effectiveness, security guarantees, interest in transacting.